2012
DOI: 10.5296/ije.v4i4.2908
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Perspectives on Sámi School Research

Abstract: What is topical in indigenous research is to view ethical guidelines and principles from their own premises and discuss the control over research activities and research findings when it comes to various disciplines and methods. The article is based on an ethnographic study that was focused on the Sámi classroom culture in Norway. The purpose of this article is to discuss those common, special ethical viewpoints that a researcher has to take into consideration when conducting Sámi educational and schooling res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The term refers to a researcher who has grown up in another culture, but through the reflection of her own experiences and values can understand the community she studies and supports its objectives. The second author has studied and developed Sámi pedagogical tools (see authors Keskitalo, Määttä, & Uusiautti 2011, 2012a, 2012bKeskitalo, Uusiautti & Määttä 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The term refers to a researcher who has grown up in another culture, but through the reflection of her own experiences and values can understand the community she studies and supports its objectives. The second author has studied and developed Sámi pedagogical tools (see authors Keskitalo, Määttä, & Uusiautti 2011, 2012a, 2012bKeskitalo, Uusiautti & Määttä 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The term refers to a researcher who has grown up in another culture, but through the reflection of her own experiences and values can understand the community she studies and supports its objectives. The second author has studied and developed Sámi pedagogical tools (see Keskitalo, Määttä & Uusiautti 2011, 2012a, 2012b, 2013Keskitalo, Uusiautti & Määttä 2012).…”
Section: Methodsmentioning
confidence: 99%
“…previous studies have shown that in indigenous schools there is need for culturally sensitive thinking (balto, 1997;cochran-smith, 1995;darnell & hoém, 1996;Keskitalo, 2003;Keskitalo, 2010;Keskitalo, määttä, & uusiautti, 2011aKeskitalo, määttä, & uusiautti, , 2011blipka, 1998). furthermore, the term cultural sensitivity is employed: it means that various cultures are noticed and considered equal and cultural special characteristics are regarded as important and worth preserving.…”
Section: Research Focusmentioning
confidence: 99%
“…however, it has been present historically for a long time. the special features of sámi education are not considered sufficiently in teaching arrangements and these problems specifically originate in the history (Keskitalo, 2010;Keskitalo, määttä, & uusiautti, 2011aKeskitalo, määttä, & uusiautti, , 2011b. as the sámi do not have self-governance that would be fully materialized, it is not possible to develop sámi education from its own premises.…”
Section: History-bound Issues Of Sámi Educationmentioning
confidence: 99%